A Cryogen Recondensing Cooling System for Scientific Experiment in the Pulsed High Magnetic Field. (April 2019) - Liu, Mengyu; Zuo, Huakun; You, Jun; Li, Liang; Wang, Shaoliang
Abstract: Traditional cryostat for scientific experiment in the pulsed high magnetic field uses liquid helium as the cooling source. To reduce the running cost and increase the operational efficiency, a cryogen recondensing cooling system based on a GM cryocooler has been developed for a 60 T measurement cell at Wuhan National High Magnetic Field Center. A helium cryostat with a recondensing system provides cooling power for sample holder insert. The bottom of the insert with a vacuum space is immersed in 4 K liquid helium bath, so that the helium gas inside the insert condenses to liquid phase at the neck tube on the top of the insert's tail. The temperature of the sample can reach 1 K and stay stable at 1.2 K for 2 hours by pumping the helium bath in the insert. The gas evaporated from the helium cryostat is recondensed by a GM cryocooler liquefier, and is circulated in a closed-loop system.